THE CONCEPT ILLAT OF USURY ON MONEY FROM THE PERSPECTIVES OF THE FOUR MADZHAB AND CONTEMPORARY ULAMA - Anam, Hoirul; Fauzi, Ahmad; Nurohman, Dede (Universitas Islam Negeri Mataram, 2024)
The concept of usury in money is still unclear when it has not been studied, apart from the differences in the opinions of the four madhhab priests regarding usury, this is also caused by the limitations of our minds to capture the wisdom and lessons revealed by Allah SWT, as well as the increasingly modern era which demands new problems. which cannot be completely resolved, therefore it has become a taboo subject since ancient times until today. This paper contains taboos to be explained more clearly. This study uses a literature approach using the literature study method based on primary material, namely the book of al-fiqh al-Islami which is motivated by problems that exist in society. With the results of the study showing that the law of usury applies to money today, because there is a legal illat similar to gold and silver (Nuqud). And with this research, it is hoped that it can add to the body of knowledge in Islamic economics.